2022
DOI: 10.1097/hnp.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Brief Stress Management Workshop for Incoming Nursing Students

Abstract: The purpose of this study was to evaluate the effectiveness of a brief stress management workshop on nursing students' perceived stress and resilience. Students who received the stress management intervention during orientation had significantly higher resilience scores and lower stress scores 1 year later during COVID-19 than the comparison group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Twenty‐five studies investigated the impact of resilience interventions on students' resilience (Table 1). Six of the sixteen studies eligible for meta‐analysis did not initially report sufficient data to include in meta‐analyses 48–50,63–65 . Missing data was obtained for two studies on request 48,63 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty‐five studies investigated the impact of resilience interventions on students' resilience (Table 1). Six of the sixteen studies eligible for meta‐analysis did not initially report sufficient data to include in meta‐analyses 48–50,63–65 . Missing data was obtained for two studies on request 48,63 .…”
Section: Resultsmentioning
confidence: 99%
“…No studies measured resilience, grit and/or mindset together. The secondary outcome of wellbeing was measured via perceived stress (n = 9) [48][49][50][51][52][53][54][55][56] , burnout (n = 4) 55,[57][58][59] and anxiety (n = 3). [60][61][62] One study reported measures of academic success via course scores.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations